Analisis Kesulitan Pembelajaran Daring Pada Mahasiswa Universitas Muria Kudus - Ika Ari Pratiwi; Muhammad Noor Ahsin; Ninda Ayu Andanawarih (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to analyze the forms of difficulties in online learning experienced by Elementary School Teacher Education students at Muria Kudus University during the covid-19 pandemic, and to describe the solutions taken by students to overcome difficulties while participating in online learning during the Covid-19 pandemic.The research method used is qualitative. The research location is on the Muria Kudus University campus in the Elementary School Teacher Education study program. The informants in this study were 20 fifth semester students who were taking PAKEM IPS courses and the learning was carried out online. Data collection techniques are filling out questionnaires, interviews, and documentation. Testing the validity of the data used using data triangulation techniques. The data analysis used in this research is qualitative data analysis developed by Miles and Huberman which consists of three stages, namely data reduction, data presentation, and verification or conclusion.The results of the study found that the forms of online learning difficulties experienced by fifth semester students were technical difficulties and difficulties in adapting. The technical difficulties referred to include limited internet quota, internet signals that are difficult to reach, unfavorable weather, sudden power outages, and limited supporting equipment. Furthermore, what is meant by difficulty in adapting is to divide the time, the home environment is not supportive, and college assignments are piling up. To overcome these difficulties, a solution is needed to overcome them. Technical difficulties in using the quota amount are overcome by saving on quota usage, difficulties in adapting the piling up college assignments are overcome by doing college assignments on time.